Motor learning and skill acquisition applications for physical education and sport - Spittle, Michael 1971- (Red Globe Press, 2021)
Integrating theory with practice, this core textbook provides a structured and sequential introduction to motor learning and motor control. Part 1 begins by introducing what motor learning is and how movement is controlled, before exploring how a learning environment may be manipulated to assist in the learning and performance of movement skills. Part 2 explores motor control from neural, behavioural and dynamic systems perspectives. Part 3 provides an overview of considerations in applying motor learning and skill acquisition principles to physical education, exercise and sports science. Chapters are illustrated with flowcharts and diagrams to aid students' understanding, and include activities and end-of-chapter review questions to consolidate knowledge.